Investigating the Influence of Human Success Factors on Success Criteria and the Moderating Effect of Project Characteristics on this Relationship in the UAE Construction Industry - Y. Altarawneh, Jaafer; Samadi, Behrang; Gharleghi, Behrooz (International Journal of Psychosocial Rehabilitation, 2020)
This paper attempted to examine the relationship between human factors such as project managers and team members competencies and projects success criteria and examine the moderating role of project characteristics on this relationship in the context of construction industry within the United Arab Emirate. The human success factors were evaluated by their influence on projects success criteria on eight criteria: schedule, budget, quality, client and team member needs, safety, absence of conflict and achieving goal. 15 indicators were identified through literature review and grouped into three distinct factors. A questionnaire has formed the basis of this research. The partial least squares (PLS) technique was applied to analyze the causal relationships between constructs and the moderating effect using the software application Smart-PLS 3.0. The paper revealed the influence of each human factor towards the success criteria of construction projects in the United Arab Emirates by valuing their standardized structural path and the moderating effect of project characteristics on the relationship between human factors and success criteria. Based on the results, project manager competencies factor has the highest influence on the success criteria of construction projects in the United Arab Emirates, and the moderating influence of project characteristics has a significant moderator effects of competencies within the construction project organization. These findings are expected to be significant contributions to UAE construction industry in toward the success completion of construction projects